Effect of astaxanthin supplementation on female fertility and reproductive outcomes: a systematic review and meta-analysis of clinical and animal studies - Arezoo Maleki-Hajiagha; Anahid Shafie; Khadije Maajani; Fardin Amidi (BMC, 2024)
Abstract Context Oxidative stress (OS) plays a harmful role in female reproduction and fertility. Several studies explored various dietary interventions and antioxidant supplements, such as astaxanthin (AST), to mitigate the adverse effects of OS on female fertility. Ameliorative effects of AST on female fertility and the redox status of reproductive organs have been shown in several animal and clinical studies. Objectives The main objective of present systematic review and meta-analysis of both animal and clinical studies was to provide a comprehensive overview of the current evidence on the effects of AST on female fertility and reproductive outcomes. The effect of AST on redox status, inflammatory and apoptotic markers in reproductive organs were included as the secondary outcomes. Data sources We systematically searched electronic databases including PubMed, Scopus, and Web of Science, until January 1, 2024, using specified search terms related to AST, female reproductive performance, and infertility, considering the diverse synonyms found in the literature for interventional studies that compared oral AST supplementation with placebo or control in human or animal models. Data extraction Two independent reviewers extracted data on study characteristics, outcomes, and risk of bias. We pooled the results using random-effects models and assessed the heterogeneity and quality of evidence. We descriptively reported the data from animal models, as meta-analysis was not possible. Data analysis The meta-analysis of clinical trials showed that AST significantly increased the oocyte maturation rate (MD: 8.40, 95% CI: 4.57 to 12.23, I2: 0%) and the total antioxidant capacity levels in the follicular fluid (MD: 0.04, 95% CI: 0.02 to 0.06, I2: 0%). The other ART and pregnancy outcomes and redox status markers did not show statistically significant changes. The animal studies reported ameliorative effects of AST on redox status, inflammation, apoptosis, and ovarian tissue histomorphology. Conclusion This systematic review shows that AST supplementation may improve assisted reproductive technology outcomes by enhancing oocyte quality and reducing OS in the reproductive organs. However, the evidence is limited by the heterogeneity, risk of bias, and small sample size of the included studies. Graphical Abstract